Relational capital wealth in an organizational context. Issue 4 (1st November 2016) - Rivera, Angel Eustorgio; Carrillo, Francisco Javier
Abstract: This paper introduces a new relational capital framework providing a relationships typology between significant agents in an organizational context and offers an integrated approach to understand relationships as a key element of organizations. Some theoretical contributions in literature on strategy and organization are considered. Following this trend, our paper proposes a general relationships classification considering the four essential relationship properties and shows that these are fundamental for the development and existence of K -events during organizational activities. Based on the elements of K -events during a relationship between significant agents, we propose that the quality of any relationship, at any level of analysis, relies on the development and measurement of certain combinations of variables that are embedded in four different categories. This study explicitly shows some possible theoretical segmentation criteria or theoretical dichotomies for analyzing the concept of relationship between agents. For theorists, it provides a conceptual base for the relationships typology, and for practitioners it identifies key elements for optimal value exchanges.